(untitled) (American Journal of Education and Technology, 2025)
The current research aimed to improve university students’ understanding of emerging and new digital technologies by developing an interactive digital platform. Consequently, three groups of undergraduate students from King Khalid University’s College of Education were randomly selected. These groups were called the empirical group (consisting of 31 students who used the Edx platform), the control group (consisting of 33 students who used the standard training strategy), and the second empirical group (consisting of 34 students who used the Blackboard platform). The research findings were analyzed using the One-Way ANOVA test. The second research hypothesis was thus rejected because, after applying the measure of awareness of Emerging digital technologies (EDT), there was a statistically significant difference at the level (0.05) in the mean scores of the first empirical group (which used the Edx platform), the second empirical group (which used the Blackboard platform), and the control group (which used the standard procedure). The findings showed that university students’ awareness of EDT increased higher when they utilized the Edx platform than when they used the Blackboard platform or the training strategy.